Religion, Inter-Community Relations, and the Kashmir Conflict - Yoginder Sikand (New Delhi Rupa & Co., 2011)
Religion, Inter-Community and the Kashmir Conflict Kashmir always remains fresh in the public memory, though not for its stunning landscapes and enchanting beauty. It is the conflict in rather over, Kashmir That assumes the center stage more often. This compilation of essays on Kashmir by Yoginder Sikand provides invaluable insights into inter-community relations in the state and leads the reader to a deeper understanding of the several layers that engulf rho Kashmir dispute. One of she most intractable international conflicts for decades, the Kashmir issue remains as complicated as ever, and a solution to it as elusive. For a more comprehensive understanding of the conflict one needs to deeply examine the sharp religious polarization in the state over the years. Consequently peace-building in Kashmir can take a more innovative turn by a revival of the more inclusive and liberal understandings of religion that can help bridge the growing communal divides among the state's inhabitants.
Include Index.
Yoginder Sikand works with the Center for the Study of Social Exclusion and Inclusive Policy us the National Lou School, Bangalore. He has worked on issues related to Muslims and Islam in South Asia and has written over a dozen books on the subject.
Keywords: Religion and politics -- India--Jammu and Kashmir -- Politics and government